Autoimmune encephalitis in Latin America. Clinical features and outcomes in pediatric and adult populations: retrospective cohort of The REAL LABIC Project - Vences, Miguel A.; Alarcon Ruiz, Christoper A.; Araujo Chumacero, Mary Marcela; Canales-Pichen, Diego; Saquisela, Victor; Domínguez-Rojas, Jesús; Melgarejo, Donoband; Reyes-Niño, Saúl; Johnston, Cintia; García-Arellano, Maricela; Suarez Loro, Mercedes Amnely; Lopes Queiroz de Lima, Cibele; et al. (Frontiers in Neurology, 2025)
IntroductionThe Autoimmune Encephalitis Registry in Latin American countries (REAL LABIC Project) is an initiative created to conduct research focused on the epidemiological and clinical aspects of autoimmune encephalitis (AE) in the region. This study describes the sociodemographic profile, clinical presentation, treatment, and follow-up outcomes of patients diagnosed with AE across multiple reference centers from Latin America.MethodsA retrospective, multicenter cohort study was conducted in 10 hospitals across 6 countries from Latin America. Medical records of pediatric and adult patients hospitalized between July 2017 and June 2022 were reviewed. Inclusion criteria were diagnostic of probable or definite AE according to consensus diagnostic criteria by Graus et al. Comparative analyses were performed between pediatric and adult groups using hypothesis contrast tests.ResultsThe study included 165 patients, 57.6% were under 18 years of age. Confirmed AE was more frequent in pediatric patients, with anti-NMDA receptor antibodies identified in 53.5% of cases (CSF/serum). The median time from symptom onset to hospital admission was 8 days, significantly shorter in pediatrics (p = 0.027). A preceding viral prodrome was more common also in pediatrics (p = 0.003). ICU admission was required in 53.9% of cases, predominantly among pediatrics (p = 0.011). First-line immunotherapy was administered in 92.1% of patients, most commonly combining corticosteroids and intravenous immunoglobulin. Early initiation of treatment (≤7 days) was associated with better response in pediatrics. At six-month follow-up, 45.5% of patients showed persistent neurological disability (mRS: 2–5). Minor cognitive impairment was the most frequent long-term sequela. In-hospital complications were reported in 53.3% of cases, and the overall mortality rate was 19.4%.ConclusionThis is the first regional multicenter study of autoimmune encephalitis in Latin America highlighting the above findings. There were no significant differences in most of the analyzed variables between pediatric and adult populations. Future research should address the strengths and limitations of this registry with the aim of gaining a broader understanding of autoimmune encephalitis in our region.